Peningkatan Pemahaman Literasi Keuangan Bagi Siswa Siswi SMK Bakti Purwokerto melalui Sosialisasi Menabung dan Investasi - Mutiasari Mutiasari; Amin Budiastuti; Herni Utami Rahmawati; Nurul Hasanah; Krishna Santosa Yusat (Institut Teknologi dan Bisnis Semarang, 2026)
This community service program aimed to improve the financial literacy of twelfth-grade students at SMK Bakti Purwokerto by strengthening their knowledge and skills in managing finances wisely. The activities were implemented through a participatory approach consisting of socialization sessions, interactive discussions, financial planning simulations, and education on safe investment practices. The materials focused on developing saving habits, financial risk management, and responsible financial decision-making. The results showed an improvement in students’ understanding and awareness of the importance of sound financial management. This improvement was reflected in positive behavioral changes, including increased saving habits and a more critical and cautious attitude toward high-risk investment offers. In addition, the program encouraged students to become agents of change who actively disseminated financial knowledge among their peers. The activities also contributed to creating a school environment that supports the implementation of healthy financial behaviors. Therefore, the participatory financial literacy program proved effective in enhancing the financial capacity and economic independence of young people while supporting sustainable social and educational development.